Communicating Space in Portugal: civic engagement? - Silva, Filipa Brandão da (2021)
This work is an analytical and pragmatic approach about the way the space industry is communicated in Portugal, establishing, simultaneously, a parallel with the current context in other countries. Knowing that the space exploration sector has such a huge impact in our lives - even if we don't realize it - it is important to make known how it can contribute to innumerous aspects in our society and how relevant it is for matters of public interest such as monitoring pandemics, climate changes, resources management among many others. Portugal always had the instinct to seek new worlds. We should look at space exploration not just as a mean to expand the reach of mankind, but also as a vital part of the solution to conquer different world challenges. Portugal has in fact an ever growing and developing space exploration industry, underlining its contribution as an inner part of the european space expansion. The space run may have begun as a search for new horizons, but the further we go the more we are able to learn about our little blue marble. Hopefully, gaining a new perspective of it and fueling the common goal of preserving it. It is now, more than ever, crucial that space activities can move beyond observation to action. The next space run may not be about competition between nations, but about humanity against the clock. Therefore, as part of science communication, communicating the space is part of a best citizenship in a way that it can result in interactions that generate mutual opportunities for learning between the scientific community and members of the public. In this article, the first results considering a content analysis of the most important public documents provided by the largests portuguese institutions in the space industry will be presented.